2012
DOI: 10.1111/j.1948-7134.2012.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence ofPeromyscus leucopusbody mass, sex, and habitat on immatureDermacentor variabilisburden

Abstract: Immature (larvae and nymph) tick burden on rodents is an important determinant of adult tick population size and understanding infectious disease dynamics. The objective of this research was to build a descriptive model for immature Dermacentor variabilis burden on Peromyscus leucopus. Mice were live-trapped on two permanent grids in an old field and an early successional forest every other month between April and October, 2006-2009. Negative binomial regression was used to examine the association between imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Heavier individuals, presumed older, generally experienced higher encounter rates with ticks (Harrison et al ., ; Mysterud et al ., ). Home range size, which is linked to body mass, is also frequently associated to tick load in small mammals and thus to the probability to acquire tick‐borne infection (Dallas et al ., ; Devevey and Brisson, ; Godsall et al ., ). For instance, Devevey and Brisson () found a positive relationship of the body mass and the home range size of male white‐footed mice ( Peromyscus leucopus ) with their nymphal tick load.…”
Section: Introductionmentioning
confidence: 99%
“…Heavier individuals, presumed older, generally experienced higher encounter rates with ticks (Harrison et al ., ; Mysterud et al ., ). Home range size, which is linked to body mass, is also frequently associated to tick load in small mammals and thus to the probability to acquire tick‐borne infection (Dallas et al ., ; Devevey and Brisson, ; Godsall et al ., ). For instance, Devevey and Brisson () found a positive relationship of the body mass and the home range size of male white‐footed mice ( Peromyscus leucopus ) with their nymphal tick load.…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate that not only would the proportional difference in dropoff be larger in females compared to males, but that the difference drop-off in females could be exacerbated by faster feeding and less time required for ticks to reach full engorgement. Multiple studies have found that tick infestation rates are skewed towards male rodent hosts [14,[55][56][57][58][59]. Bank vole males have larger home ranges than females [60,61], and therefore roam around more than females.…”
Section: Plos Onementioning
confidence: 99%
“…The basic starting concept is that each species of tick and its animal hosts are found within specific ranges of environmental variables (temperature, humidity, ecotypes), which support their reproduction and individual survival ( 123 ), so that the existing climate and environmental parameters associated with an agent define a set of conditions necessary for the predicted existence of a particular population in a very specific small area or averaged over a much larger region ( 122 ). The geographical range of a tick population depends on many parameters ranging from the life cycle of the tick, abundance of its hosts, and anthropogenic influences on vegetation, land use, and host displacement ( 124 , 125 ). The Mediterranean region is expected to experience the greatest changes in risk of tick-borne infections in Europe due to predicted increases in average temperature and decreases in average rainfall.…”
Section: Modeling Of Tick-borne Rickettsial Diseasesmentioning
confidence: 99%
“…Thus, it seems crucial to evaluate the actual burden of ticks on the host animal populations to accurately measure this variable. To address these questions, Dallas et al ( 124 ) evaluated the association of nymphal and larval D. variabilis with its primary mammal host, P. leucopus and computed the tick burden in relation to other host variables, including mass, sex, and habitat ( 124 ). Consistent with other rodent-tick systems, this study demonstrated that the burden of immature D. variabilis is positively associated with male mice of higher body mass captured in the field habitat ( 124 ).…”
Section: Modeling Of Tick-borne Rickettsial Diseasesmentioning
confidence: 99%
See 1 more Smart Citation